2021
DOI: 10.1126/sciimmunol.abg7506
|View full text |Cite
|
Sign up to set email alerts
|

c-MAF–dependent perivascular macrophages regulate diet-induced metabolic syndrome

Abstract: Macrophages are an essential part of tissue development and physiology. Perivascular macrophages have been described in tissues and appear to play a role in development and disease processes, although it remains unclear what the key features of these cells are. Here, we identify a subpopulation of perivascular macrophages in several organs, characterized by their dependence on the transcription factor c-MAF and displaying nonconventional macrophage markers including LYVE1, folate receptor 2, and CD38. Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 105 publications
1
26
0
Order By: Relevance
“…3F) was most likely directly due to the loss of IL-6 from the TME. Recent data demonstrated that the transcription factor c-MAF was vital to the development of Lyve-1 + Pv macrophages in healthy tissues ( 44 ), and we sought to establish whether c-MAF signaling may account for the Lyve-1 + macrophage phenotype observed through IL-6 stimulation. IL-6 signaling is associated with the JAK/STAT3 pathway ( 45 ), however, STAT3 has been linked to the expression of c-MAF via the basic leucine zipper transcription factor ATF-like, Batf in T follicular helper cells ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3F) was most likely directly due to the loss of IL-6 from the TME. Recent data demonstrated that the transcription factor c-MAF was vital to the development of Lyve-1 + Pv macrophages in healthy tissues ( 44 ), and we sought to establish whether c-MAF signaling may account for the Lyve-1 + macrophage phenotype observed through IL-6 stimulation. IL-6 signaling is associated with the JAK/STAT3 pathway ( 45 ), however, STAT3 has been linked to the expression of c-MAF via the basic leucine zipper transcription factor ATF-like, Batf in T follicular helper cells ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, surprisingly, in homeostatic tissues, tissue resident Lyve-1 + macrophage populations also expressed HO-1. We identified in vitro that c-MAF signaling was required for Lyve-1, HO-1 and CD206 expression on BMDMs in response to IL-6 and could link these markers on tissue resident macrophages in non-inflammed healthy tissues which have recently been demonstrated also to be c-MAF-dependent ( 44 ). Although the signal for c-MAF in healthy tissues is unknown, it could explain the unexpected high expression of HO-1 which is generally considered as a stress- or inflammation-inducible enzyme ( 30 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each MP cluster was then identified based on their top 30 cluster-defining genes ( Fig 5E ). MPs in clusters 0 and 5 highly expressed Lyve1 , Mrc1 , Maf , and Timd4 , thus corresponding to tissue-resident Tim-4 + MPs (De Schepper et al ., 2018; Dick et al ., 2022; Moura Silva et al ., 2021). MPs in clusters 0 and 5 co-expressed Cd4 but not Ccr2 , consistent with our flow cytometric classification ( Fig 5F ).…”
Section: Resultsmentioning
confidence: 99%
“…MPs in clusters 0 and 5 co-expressed Cd4 but not Ccr2 , consistent with our flow cytometric classification ( Fig 5F ). Interestingly, MPs in cluster 5, enriched in the TLO, expressed higher levels of Folr2 , which was shown to be expressed in gut and brain c-MAF-dependent perivascular MPs involved in metabolic regulation (Moura Silva et al ., 2021). Consistent with previous reports, pathway analysis demonstrated that MPs in clusters 0 and 5 were enriched in endocytosis and vesicle-mediated transport pathways and mediated tissue homeostatic functions, including synapse pruning ( Fig 5G, Fig S4E ).…”
Section: Resultsmentioning
confidence: 99%
“…In diabetic mice with gastroparesis, an increased number of MMs 25 coincides with a higher level of MMs expressing proinflammatory markers, 26 which can depend on increased recruitment of monocytes. A recent study 27 identified a population of MMs closely associated with blood vessels in the GI muscularis called perivascular MMs. This population of MMs is regulated by the transcription factor Maf, which also controls the expression of several genes associated with the anti-inflammatory MMs.…”
Section: Originmentioning
confidence: 99%